Efficient treatment of mercury(Ⅱ)-containing wastewater in aerated constructed wetland microcosms packed with biochar. (March 2022) - Chang, Junjun; Peng, Dongliang; Deng, Shengjiong; Chen, Jinquan; Duan, Changqun
Abstract: Effective removal of mercury (Hg) pollutants from contaminated water/wastewater to prevent severe environmental pollution is of great significance due to the extremely high toxicity of Hg. In this study, granular biochar and gravel (control) were packed into intermittently aerated constructed wetland (CW) microcosms to treat Hg(Ⅱ)-containing wastewater over 100 d. The results showed that the biochar-filled CWs exhibited notably better Hg(Ⅱ) removal than the gravel systems by facilitating chemical and microbial Hg(Ⅱ) reduction and volatilization and promoting plant growth and Hg assimilation. More than ten times more Hg was absorbed by the plants ( L. salicaria ) in biochar CWs than in the gravel systems, with the roots acting as the major sink. In contrast, substrate binding in a predominantly oxidizable fraction was the dominant pathway for Hg removal in the gravel CWs. Biochar substrates also exhibited higher levels of COD, N and P removal, and Hg(Ⅱ) import impacted the removal of these pollutants only slightly. Filling material played a more crucial role than Hg input in shaping the microbial communities in the CWs. The proportions of some dominant genera, including Arenimonas, Lysobacter, Micropruina and Hydrogenophaga, increased in the presence of Hg, implying their tolerance to Hg toxicity and potential roles in Hg detoxification in the CWs. Granular biochar-based CW has high potential for treating Hg(Ⅱ)-contaminated wastewater. Graphical abstract: Image 1 Highlights: Granular biochar-filled CWs were applied to treat Hg(Ⅱ)-containing wastewater. Biochar substrates facilitated Hg volatilization and phytoremediation. Biochar CWs were more effective in removing COD, N and P than gravel systems. Hg(Ⅱ) input slightly decreased the nutrient removal efficiencies of CWs. Effect of Hg on the microbial communities in CWs was related to substrate type.